102 Translating logistical challenges into service improvement: MS infusional services during the covid-19 pandemic. Issue 6 (27th May 2022) - Ramsay, Stephen; Magill, Fiona; Cartmill, Glenn; Goldsmith, Grainne; McKee, Jon; Kennedy, Fiona; Droogan, Aidan; Hughes, Stella; McDonnell, Gavin
Abstract : Background: Providing care to Multiple Sclerosis (MS) patients has been a challenge during the Covid-19 pandemic. Locally, surge plans necessitated an abrupt change of facility for infusional services, now supervised by MS nurses, from an acute site (Royal Victoria Hospital, RVH) to a non-acute site at Musgrave Park Hospital (MPH). Objective: To assess patient satisfaction with MS infusional therapies at a new, non-acute location and supervision of the service by MS Specialist nurses in comparison with previous arrangements. Methods: Anonymous patient surveys were developed and collected in order to assess patient demo- graphics and levels of satisfaction across various service domains. Results: All 120 offered surveys were returned. Overall, 97% recorded a satisfaction score of ≥8/10 (0–10, 10 = extremely satisfied). Key areas of improvement: difficulty parking (0.8% vs 50% in RVH), difficulty of unit access (0.8% vs 38% previously), appointment punctuality (95% on time vs 35% previously), and comfort (83% vs 55% previously). Thematic analysis revealed several key improvement areas: access to MS nursing knowledge, cannulation, and punctuality. Conclusion: The urgently relocated service, with better access and specialist nursing input, was associ- ated with substantial improvements in patient experience. Despite current unprecedented pressures on healthcare delivery, unique opportunities remain for service improvement. sramsay03@qub.ac.uk|ABN Bursary 76